Configuration Design and Topology Description of the Power Release Latch with Variable Topology Characteristic - Bai Lele; Hang Lubin; Liu Zhe; Miao Hong; Huang Xiaobo; Guo Hui; Chen Yong; Hua Yong (Jixie chuandong)
The power-release function of the vehicle latch is the physical basis for passengers' non-physical operation mode to enter the vehicle and plays a vital role in the intelligent automatic door system. Aiming at the demand of dual branch chains cooperative drive of the electrical lock and the power release， also the non-interference between the multiple kinematic branch chains of the vehicle latch， a novel power release kinematic chain with the variable topological characteristic is constructed. Based on the synthesis theory of the topological structure for planar mechanism， the intermittent mechanism of incomplete gear is synthesized into the power release kinematic chain. The incidence matrix is used to study the topological structure state of the power release branch chain. Furthermore， through the physical prototype fabrication and function experiment of the novel vehicle latch， the feasibility of the power release vehicle latch is verified. This research provides a novel idea for the design of the kinematic chain of the vehicle intelligent latch.